2013
DOI: 10.1016/j.bbamem.2013.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Function of site-2 proteases in bacteria and bacterial pathogens

Abstract: Site-2 Proteases (S2Ps) are a class of intramembrane metalloproteases named after the founding member of this protein family, human S2P, which cleaves Sterol Regulatory Element Binding Proteins which control cholesterol and fatty acid biosynthesis. S2Ps are widely distributed in bacteria and participate in diverse pathways that control such diverse functions as membrane integrity, sporulation, lipid biosynthesis, pheromone production, virulence, and others. The most common signaling mechanism mediated by S2Ps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 79 publications
0
59
0
Order By: Relevance
“…Bacterial S2Ps are involved in cleavage of transcriptional regulators, mainly transmembrane-tethered antisigma factors, which after cleavage activate sigma factor regulons (reviewed by Schneider et al [15]). In the pathogen Mycobacterium tuberculosis, three putative S2Ps exist: Rip1, 2, and 3.…”
Section: Box 1 the Functions Of Intramembrane Proteasesmentioning
confidence: 99%
“…Bacterial S2Ps are involved in cleavage of transcriptional regulators, mainly transmembrane-tethered antisigma factors, which after cleavage activate sigma factor regulons (reviewed by Schneider et al [15]). In the pathogen Mycobacterium tuberculosis, three putative S2Ps exist: Rip1, 2, and 3.…”
Section: Box 1 the Functions Of Intramembrane Proteasesmentioning
confidence: 99%
“…I-CLiPs are found in all kingdoms of life and can be classified into several families, based on amino acid sequence homology and the residues involved in catalysis, including S2P proteases (zinc metalloproteinases), rhomboid proteases (serine proteases) and g-secretase/signal peptide peptidases (aspartyl proteases) (Ha, 2009;Wolfe, 2009;Urban, 2013). Recent research revealed that these I-CLiPs play important roles in a variety of biological processes, including lipid homeostasis, EGF signaling, Notch signaling, stress response and bacterial sporulation and virulence (Nakayama et al, 2011;Kroos and Akiyama, 2013;Rawson, 2013;Schneider and Glickman, 2013;Lastun et al, 2016). I-CLiPs have been associated with several diseases such as Alzheimer's disease and Parkinson's disease (Walder et al, 2005;De Strooper et al, 2012;Song et al, 2015;Spinazzi and De Strooper, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…RIP is performed by intramembrane proteases-an integral membrane proteins able to hydrolyze a transmembrane helix of their substrates and release them from the membrane. This relatively recently discovered class of proteases occurs ubiquitously in all living organisms from bacteria through archaea to eukarya (Adam 2013;Schneider and Glickman 2013;Knopf et al 2012). The first described intramembrane protease was site-2 protease (S2P), identified in human cells in 1997 (Rawson et al 1997).…”
Section: Introductionmentioning
confidence: 99%